2018
DOI: 10.7554/elife.39720
|View full text |Cite
|
Sign up to set email alerts
|

Selective agonist of TRPML2 reveals direct role in chemokine release from innate immune cells

Abstract: Cytokines and chemokines are produced and secreted by a broad range of immune cells including macrophages. Remarkably, little is known about how these inflammatory mediators are released from the various immune cells. Here, the endolysosomal cation channel TRPML2 is shown to play a direct role in chemokine trafficking and secretion from murine macrophages. To demonstrate acute and direct involvement of TRPML2 in these processes, the first isoform-selective TRPML2 channel agonist was generated, ML2-SA1. ML2-SA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 74 publications
1
94
0
Order By: Relevance
“…The release is most likely mediated via the early/recycling endosomal pathway, since activation of TRPML2 by ML2-SA1 promotes trafficking through this pathway. In addition, Plesch et al found that direct activation of TRPML2 leads to enhanced recruitment of macrophages (5). These findings by Sun et al and Plesch et al strongly suggest that TRPML2 plays a crucial role in the release of CCL2 and likely other chemokines as well as in the stimulation of macrophage migration.…”
Section: Chapter I: Innate Immune System Macrophagesmentioning
confidence: 90%
See 3 more Smart Citations
“…The release is most likely mediated via the early/recycling endosomal pathway, since activation of TRPML2 by ML2-SA1 promotes trafficking through this pathway. In addition, Plesch et al found that direct activation of TRPML2 leads to enhanced recruitment of macrophages (5). These findings by Sun et al and Plesch et al strongly suggest that TRPML2 plays a crucial role in the release of CCL2 and likely other chemokines as well as in the stimulation of macrophage migration.…”
Section: Chapter I: Innate Immune System Macrophagesmentioning
confidence: 90%
“…All three channels are regulated by the phosphoinositide PI(3,5)P 2 , a major component of endolysosomal membranes and by luminal pH (1,(3)(4)(5). Thus, TRPML1 is most active at highly acidic pH as found in lysosomes while TRPML2 and TRPML3 are more active at higher pH as it occurs in early and recycling endosomes (1,(3)(4)(5). TRPML1 activity already decreases under mild acidic conditions (pH 5.5; Figure 1) and is lowest at neutral conditions (4).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are two other members in the TRPML subfamily, TRPML2 and TRPML3, encoded by MCOLN2 and MCOLN3 genes. Like TRPML1, they are active in late endosomes/lysosomes; in addition, TRPML2 and TRPML3 are active in early endosomes, and TRPML2 also in recycling (Chen et al, 2017;Plesch et al, 2018). They have not been correlated with neurodegeneration in humans so far.…”
Section: Introductionmentioning
confidence: 98%